1980
DOI: 10.1002/jcu.1870080609
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian imaging by ultrasound: An attempt to define a reference plane

Abstract: The use of ultrasound to study ovarian function was established by our group. Ultrasound measurements of follicular diameters were found to be helpful for assessing follicular growth and development and for diagnosing and treating infertile women. Because of difficulties in ovarian visualization (differentiation between a more lateral part of the uterus and the ovary), the definition of a reference plane is necessary, especially to make this new technique reproducible. On the basis of the anatomic situation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Hackeloer has suggested that preliminary visualization of the infundibula-pelvic ligaments could reduce this source of error. 10 However, in our experience, this cannot always be achieved, especially in routine investigations with less sophisticated real· time equipment. Furthermore, there can be conditions in which pelvic varices may even require Doppler devices in order to be differentiated from polycystic ovarian parenchyma.…”
Section: Discussionmentioning
confidence: 88%
“…Hackeloer has suggested that preliminary visualization of the infundibula-pelvic ligaments could reduce this source of error. 10 However, in our experience, this cannot always be achieved, especially in routine investigations with less sophisticated real· time equipment. Furthermore, there can be conditions in which pelvic varices may even require Doppler devices in order to be differentiated from polycystic ovarian parenchyma.…”
Section: Discussionmentioning
confidence: 88%
“…All of the ultrasound scans were recorded on videotape. We identified the ovaries with the use of the full-bladder technique (11,12) and measured them in three dimensions. The length and depth measurements were obtained from parasagittal views; the width measurements were obtained from transverse views.…”
Section: Pelvic Ultrasonography and Classification Of Ultrasound Patt...mentioning
confidence: 99%
“…The ovarian artery is very tortuous, especially when it is close to the ovary [ 15 ]. The blood supply to the ovary also comes from the ovarian branch of the uterine artery, which joins with the ovarian artery, close to the ovary [ 16 ].…”
Section: Ovarian Blood Flowmentioning
confidence: 99%